Natural history and management of Fanconi anemia patients with head and neck cancer: A 10‐year follow‐up. (20th October 2015) - Kutler, David I.; Patel, Krupa R.; Auerbach, Arleen D.; Kennedy, Jennifer; Lach, Francis P.; Sanborn, Erica; Cohen, Marc A.; Kuhel, William I.; Smogorzewska, Agata
Abstract : Objectives/Hypothesis: To describe the management and outcomes of Fanconi anemia (FA) patients with head and neck squamous cell carcinoma. Study Design: Cohort study. Methods: Demographic information, prognostic factors, therapeutic management, and survival outcomes for FA patients enrolled in the International Fanconi Anemia Registry who developed head and neck squamous cell carcinoma (HNSCC) were analyzed. Results: Thirty‐five FA patients were diagnosed with HNSCC at a mean age of 32 years. The most common site of primary cancer was the oral cavity (26 of 35, 74%). Thirty patients underwent surgical resection of the cancer. Sixteen patients received radiation therapy with an average radiation dose of 5, 050 cGy. The most common toxicities were high‐grade mucositis (9 of 16, 56%), hematologic abnormalities (8 of 16, 50%), and dysphagia (8 of 16, 50%). Three patients received conventional chemotherapy and had significant complications, whereas three patients who received targeted chemotherapy with cetuximab had fewer toxicities. The 5‐year overall survival rate was 39%, with a cause‐specific survival rate of 47%. Conclusions: Fanconi anemia patients have a high risk of developing aggressive HNSCC at an early age. Fanconi anemia patients can tolerate complex ablative and reconstructive surgeries, but careful postoperative care is required to reduce morbidity. The treatment of FA‐associated HNSCC is difficult secondary to the poor tolerance of radiation and chemotherapy. However, radiation should be used for high‐risk cancers due to the poor survival in these patients. Level of Evidence: 4. Laryngoscope, 126:870–879, 2016